Dr Mahathir's selected letters to world leaders - Mahathir Mohamad Tun 1925- (Marshall Cavendish Editions, 2008)
The seventy-one letters by Dr Mahathir, Bush, Chirac, Blair, Thatcher and Prince Charles (among others) are unique as they interpret and argue their contrasting positions on terrorism, globalisation, economic and diplomatic relations, and war and conflicts. The correspondence presents a less-than-ideal world for the reader to inhabit. Their correspondence was transparent, solid, informative, and sometimes strong. The memories they and their words leave behind are always startling. Dr Mahathir writes directly, in his own recognisable voice and style, a unique correspondence by a remarkable Malaysian former prime minister. An excellent book to be enjoyed, on many different levels, by all who love politics, diplomacy and international relations. Never before published, these letters are written in a clear and easy-to-understand style.